Virtual auctions / Louis Tan Han Chooi - Louis Tan, Han Chooi (2002)
Virtual Auctions is about developing an e-auction system for online auctioning off general merchandise to bidders in specialized auctions such as travel auction, computer auction, car auction, etc. The system will allow bidders to do online registration and bidding, which could be for auctioning off many interesting, bizarre and exciting items such as watches, antiques etc. In the development of this system, there are several stages involved, which we will see in the following chapters of this report. Firstly there will be an Introduction chapter where the objectives and scope of this project is determined. Also there is a part where the system development approach will be explained together with the methodology to be used in the development of the Virtual Auctions system. Then a Literature Review is done in the second chapter. The purpose of literature review is to gather as much relevant information as possible about the Virtual Auctions project. It is very important as it recognizes other projects that might have similar characteristics to this project. Therefore, a literature review will be able to help the developer know the features offered by existing system. After gathering relevant information about the project in the Literature Review, we move on to the Analysis chapter where the systems analysis is done. The systems analysis stage is where all the requirements of the Virtual Auctions system are analyzed and a requirements model is produced as a result. Then the next chapter will be the Design chapter where the proposed system will be designed according to the requirements specifications done in the analysis phase. It is hoped that the development of this system will give much invaluable experience and knowledge in the system development field. It is also a vision for this system to achieve its objectives and to provide a better solution to the local web-based auction community.